2023
DOI: 10.1021/acs.analchem.3c04263
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Redox Cycling in an Organic Photoelectrochemical Transistor: Toward Dual Chemical and Electronic Amplification for Bioanalysis

Yu-Ting Huang,
Ke-Xin Xu,
Xing-Shi Liu
et al.

Abstract: The organic photoelectrochemical transistor (OPECT) has been proven to be a promising platform to study the rich light− matter−bio interplay toward advanced biomolecular detection, yet current OPECT is highly restrained to its intrinsic electronic amplification. Herein, this work first combines chemical amplification with electronic amplification in OPECT for dual-amplified bioanalytics with high current gain, which is exemplified by human immunoglobulin G (HIgG)-dependent sandwich immunorecognition and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Under visible light illumination, the alteration of the gate potential results in a sensitive change in I DS . In essence, the OPECT device operates on a photovoltage at the gate/electrolyte interface, enabling photochemical modulation of the channel . In more specific terms, in the dark state, PEDOT + maintains its oxidation state, giving the channel a high conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under visible light illumination, the alteration of the gate potential results in a sensitive change in I DS . In essence, the OPECT device operates on a photovoltage at the gate/electrolyte interface, enabling photochemical modulation of the channel . In more specific terms, in the dark state, PEDOT + maintains its oxidation state, giving the channel a high conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 7A, under the same illumination and working electrode, the photocurrent intensity (I G = I G,light �I G,dark ) of the traditional PEC method is 0.15 μA, In essence, the OPECT device operates on a photovoltage at the gate/electrolyte interface, enabling photochemical modulation of the channel. 34 In more specific terms, in the dark state, PEDOT + maintains its oxidation state, giving the channel a high conductivity. However, under visible light, the presence of V photo induces cation injection into the PEDOT + :PSS − channel, producing PEDOT 0 , resulting in a low conductivity of the channel.…”
Section: Pec Performance Analysis Of Cu-mof and Its Compositesmentioning
confidence: 99%
“…Based on the fusion between organic electrochemical transistor (OECT) and photoelectrochemistry (PEC), the newly emerged organic photoelectrochemical transistor (OPECT) composing three terminals of photoresponsive gate (G), source (S), and drain (D) have shown substantial potential in the development of next-generation organic devices with intrinsic signal amplification, temporal-spatial light controllability, and diverse applications in, e.g., bioanalysis, , optoelectronics, and neuromorphic engineering. , Principally, according to different signaling mechanisms stemming from the pristine doping state of the conducting channels, existing OPECT operations could be divided into depletion and accumulation modes. Light impact on specific photogates could induce additional photopotential and alter the potential distribution of the two solid–liquid interfaces. Previous studies have revealed that photoanodes generating positive photovoltage are more suitable for depletion-mode channels, while photocathodes generating negative photovoltage are more suitable for accumulation-mode channels. These studies hinted at an either-or situation yet ignored another possibility: could both the photoanode and photocathode be simultaneously utilized for enhanced OPECT bioanalysis?…”
Section: Introductionmentioning
confidence: 99%